2020
DOI: 10.3390/agronomy10081174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrification Inhibitors on N2O Emissions after Cattle Slurry Application

Abstract: Cattle slurry injection (INJ) has shown to be an efficient measure to reduce ammonia (NH3) losses from soils but it might also significantly increase nitrous oxide (N2O) emissions, which can dominate the total greenhouse gas (GHG) release in silage maize production (Zea mays L.). Nitrification inhibitors (NIs) are known for their potential to mitigate N2O. Therefore, we tested the effect of NIs added to cattle slurry before INJ on N2O fluxes from a Haplic Luvisol under silage maize in southwest Germany. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…This effect is comparable with the lower mean annual N 2 O emissions (up to 46%) reported when cattle slurry was injected with commercial NIs, including 2-chloro-6-(trichloromethyl) pyridine (nitrapyrin), on Haplic Luvisol under silage maize in Germany (Herr et al, 2020). This medium-term comparison between the five commercially available NIs showed no difference in N 2 O fluxes, crop yield, or N removal when cattle slurry was mixed with NIs before injection (Herr et al, 2020). A metaanalysis on the use of nitrapyrin with slurry in corn production concluded that the manure applied with this inhibitor increased the crop yield by 7%, improved the N retention in the soil by 28%, and decreased N 2 O emissions by 51% (Wolt, 2004).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This effect is comparable with the lower mean annual N 2 O emissions (up to 46%) reported when cattle slurry was injected with commercial NIs, including 2-chloro-6-(trichloromethyl) pyridine (nitrapyrin), on Haplic Luvisol under silage maize in Germany (Herr et al, 2020). This medium-term comparison between the five commercially available NIs showed no difference in N 2 O fluxes, crop yield, or N removal when cattle slurry was mixed with NIs before injection (Herr et al, 2020). A metaanalysis on the use of nitrapyrin with slurry in corn production concluded that the manure applied with this inhibitor increased the crop yield by 7%, improved the N retention in the soil by 28%, and decreased N 2 O emissions by 51% (Wolt, 2004).…”
Section: Introductionsupporting
confidence: 73%
“…It has been reported that NIs applied to cattle slurry decrease N 2 O losses by 60% after its surface application in grassland soils from temperate regions and NI efficiency was lower in spring than that in autumn (Merino et al, 2002(Merino et al, , 2005. This effect is comparable with the lower mean annual N 2 O emissions (up to 46%) reported when cattle slurry was injected with commercial NIs, including 2-chloro-6-(trichloromethyl) pyridine (nitrapyrin), on Haplic Luvisol under silage maize in Germany (Herr et al, 2020). This medium-term comparison between the five commercially available NIs showed no difference in N 2 O fluxes, crop yield, or N removal when cattle slurry was mixed with NIs before injection (Herr et al, 2020).…”
Section: Introductionmentioning
confidence: 68%
“…For the calculation of annual N 2 O emission, N 2 O fluxes from each treatment and experimental year were cumulated, assuming constant flux rates between two gas samplings. Methane (CH 4 ) fluxes were also detected but are reported elsewhere ( Herr , ).…”
Section: Methodsmentioning
confidence: 79%
“…In the injection treatment, the circular base frames (inner diameter: 0.3 m) were placed area‐representative; 7% of the base frame area was covered by the area above the injection slot, 93% by the area next to the injection slot. Methodological evaluation and area‐representative placement of the dark, vented chambers were described in detail by Herr (). All frames were installed close to the maize row ( Gassner , ).…”
Section: Methodsmentioning
confidence: 99%
“…According to IPCC (2019) 1% of NH 3 -N losses was assumed to be re-deposited as N 2 O-N. Soil organic C stocks were presumed to be stable over the experimental period, thus, CO 2 fluxes were not considered for the calculation of total GWP (Herr et al, 2020). Water filled pore space (WFPS) was calculated by Equation (6) using the measured volumetric water content (WC vol ) and porosity (P),…”
Section: Statistics and Calculationsmentioning
confidence: 99%